2009
DOI: 10.1364/ao.48.005647
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a spatial light modulator using thermally tunable grating and a thin-film heater

Abstract: We propose the application of a thermally tunable grating as a spatial light modulator. The grooves of a square-well grating are filled with a liquid whose refractive index depends on temperature. The variation of optical characteristics of such a grating with respect to temperature is investigated theoretically and also by simulation and experiment. A thin-film heater is then used as a heat source. The relation between intensity of the first order of diffraction versus power consumption of the thin-film heate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…13c,d,e. It can be shown that the intensity of the first order of diffraction can be calculated as follow (Riahi et al, 2009):…”
Section: Principle Of the Methodsmentioning
confidence: 99%
“…13c,d,e. It can be shown that the intensity of the first order of diffraction can be calculated as follow (Riahi et al, 2009):…”
Section: Principle Of the Methodsmentioning
confidence: 99%